A pan-European perspective of third space professionals located in learning and teaching centres - Graham William Scott; Manuel Joao Costa; Mike Ewen; Catherine Lillie; Helene Peterbauer; Oliver Vettori; Carina Weiß; Johanna Warm; Aune Valk; Mari Karm; Hanna-Britt Soots; Guðrún Geirsdóttir; et al. (Journal of Learning Development in Higher Education)
During 2023, the European University Association brought together members of 10 Learning and Teaching Centres from 10 European countries to explore the development and strategic benefits of Learning and Teaching Centres. Through critical self-reflection and active dialogue, the group developed a consensus on the positive value of active collaboration between academic, administrative, and third space professional staff in the effective functioning of Learning and Teaching Centres. They also recognised two pan-European challenges faced by centres and those working within them, namely institutional position and trust and credibility, in light of which they proposed two lines of enquiry that should be the focus of further pan-European discourse and action.